Desain Ruang Seminar Desa Cimenyan, Bandung, Jawa Barat, Berbasis Partisipasi Pengguna untuk Peningkatan Pelayanan Warga - Anjar Primasetra; Tyas Santri; Siti Anah Kunyati; Romi Akmaludin Fadillah; Dimas Erich Fernandes (Jurnal Pengabdian Tri Bhakti, 2026)
Cimenyan Village, Bandung one of the community partners of Universitas Langlangbuana Bandung initiated the development of a seminar room within the village office. The university’s community service team contributed through a user-participatory seminar room design program. This initiative represents a continuation of earlier community service activities, including the interior design of several village office facilities such as a pantry, meeting room, and podcast room, all aimed at improving public service quality for residents. The intervention was considered urgent due to the existing seminar space frequently experiencing capacity overload, despite its essential role in public outreach activities and hosting official guests. The program sought to optimize village facilities through several stages: preliminary studies, field measurements, participatory discussions to gather input from village officials, concept development, and the preparation of planning drawings along with a detailed Budget Plan (RAB). The scope of this activity was limited to design assistance and planning support and did not include physical construction. The participatory approach ensured that the resulting design aligned with user needs, enhanced comfort, and provided transparent cost projections for the renovation plan. The final outcome consisted of an extension design for the seminar room along with supporting spaces, complete with measurable cost estimates, which is expected to address capacity issues and improve service performance at the Cimenyan Village Office.